Students’Translation Strategy in Translating Proper Noun - Jemaah jemah; Roganda Eko Sutra Manullang (English Language Teaching Prima Journal (ELT), 2021)
ABSTRACT This review manages the understudies' translation technique in deciphering thing. This review was led by utilizing graphic subjective exploration. This review was done in SMK Sandhy Putra 2 Medan. The subject of this examination were the understudies in SMK sandhy Putra 2 Medan. The examination was led in two days. The main day, the scientist gave test to the understudies. The subsequent day, the scientist directed meeting the understudies. The instruments utilized in this examination were test and meeting. The test given used to know the understudies' translation procedure in deciphering thing while meet led to know the understudies' concern in interpreting thing. In light of the investigation of information, it was found that there were three sorts of translation procedure found, in particular modify, replacement of sound and unique structure. Key words: translation, proper noun